Hubungan Work Engagement Dengan Burnout Terhadap Produktivitas Kerja Karyawan Di Perusahaan - Arifani zakiah aulianti (CV. ITTC INDONESIA, 2023)
Work Engagement is defined as a positive motivational state of vigor, dedication, and absorption, while burnout refers to a state of exhaustion and apathy towards work. In this article, we will discuss both concepts used in the literature and their main definitions. This research was conducted through a quantitative approach involving hypothesis testing. Additionally, we examine individual and situational predictors to examine the most important aspects of burnout and work engagement. Additionally, we review the impact of burnout and engagement, and we integrate the research results with job demands—resources theory. Although both work engagement and burnout are related to important work-related outcomes, burnout appears to be more strongly related to health outcomes, and work engagement appears to be more strongly related to motivational outcomes. We talk every day, and there are small changes in engagement and fatigue.